PENGUATAN KARAKTER INTEGRITAS PELAJAR MELALUI SOSIALISASI ANTI-KORUPSI DI SMA DAN SMK KOTA DUMAI - Amiroel Oemara Syarief; Merina Pratiwi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This Community Service activity aims to strengthen students’ integrity character through anti-corruption socialization programs at senior high schools and vocational high schools in Dumai City. The background of this activity is based on the importance of instilling values of honesty, responsibility, and anti-corruption attitudes from an early age as an effort to prevent corrupt behavior in the future. The implementation methods include socialization and counseling on corruption issues and integrity values, interactive discussions, the presentation of case studies related to students’ daily lives, and evaluation through question-and-answer sessions and simple questionnaire distribution. The results indicate an improvement in students’ understanding of the concept of corruption and the importance of integrity, as well as increased awareness in applying these values within the school environment and daily life. This activity is expected to serve as an initial step in shaping a generation that is ethical, integrity-oriented, and committed to anti-corruption values..